CLINICAL SAFETY OF TREATMENT WITH ZILEUTON, 5-LOX INHIBITOR, DURING ACUTE INFLAMMATORY REACTION IN NILE TILAPIA (Oreochromis niloticus) - COSTA, C. C.; OLIVEIRA, S. L.; ARACATI, M. F.; RODRIGUES, L. F.; COLTURATO, L.; MONTASSIER, H. J.; BELO, M. A. A. (Ars Veterinaria, 2022)
Zileuton is an inhibitor of the 5-lipoxygenase enzyme that transforms essential fatty acid (EFA) substrates into leukotrienes (LTB4, LTC4, LTD4 and LTE4), but little is known about the use of this drug in teleost fish. Therefore, the objective of this study was to evaluate the clinical safety of treatments with 2,25 mg and 4,50 mg of zileuton/Kg-1 (bodyweight), administered orally in the diet, through biochemical and hematological analysis during the acute inflammatory reaction in Nile tilapia (Oreochromis niloticus), induced by Aeromonas hydrophila bacterins. The study used eighty tilapias, conditioned in 20 tanks (n=4), constituting the following treatments: T0 (control), T1 (2,25 mg zileuton) and T2 (4,50 mg zileuton), being sampled eight animals per treatment in three periods: 6, 24 and 48 hours post-inoculation, and a 10th group consisting of fish without any type of stimulus to obtain the reference values. In order to evaluate and determine the blood count and serum biochemical, it was necessary to collect blood samples. The hematology results of the tilapia treated with zileuton did not reveal alterations between tilapia subjected to different treatments and control fish (T0). The liver cytotoxicity analysis of tilapias treated with zileuton did not reveal significant (p≥0,05) alterations in AST and ALT serum enzymatic activity. The study of tilapia blood total protein showed decrease in the T1 group at 48 HPI. As the treatment time progressed, the results indicated decrease in the serum albumin levels for T2 group at 24 HPI. The determination of serum biochemichal of creatinine, cholesterol, triglycerides, and glucose did not differ statistically between treatments. The results observed in the hematological and biochemical analyzes allows to conclude that zileuton administered orally, at doses of 2,25 and 4,50 mg/Kg-1 (body weight) demonstrated to be clinically safe.